Electric Car Chassis Design and Analysis by Using CATIA V5 R19 - Zainal Ariffin, Ahmad Zainal Taufik; Mat Nuri @ Md Din, Nur Rashid; Ahmad Mansor, Mazlan; Hassan, Muhammad Zahir; Abdul Latif, Mohd Faruq (IOSR Journal of Mechanical and Civil Engineering (IOSR-JMCE), 2014)
The evolution of computer aided design (CAD) systems and related technologies has promoted the development of software for the east of chassis modeling. It visualizes the main outputs of the model, which consist in numeric data and graphic elements. This reduces the simulation time dramatically and enables the optimization process to come to successful results. This paper presents an electric car chassis design by using the commercial design software package, CATIA V5 R19. The design of the chassis with adequate stiffness and strength is the aim of this project. The material used is mild steel AISI 1018 with 386 MPa of yield strength and 634 MPa of ultimate strength. The result shows that the critical point of stress and displacement occurred in the middle of the side members in all loading conditions, maximum stresses are below the yield stress. The final products for the design have been fabricated successfully.